Using Population Pharmacokinetic Modeling and Monte Carlo Simulations To Determine whether Standard Doses of Piperacillin in Piperacillin-Tazobactam Regimens Are Adequate for the Management of Febrile Neutropenia - Sime, Fekade Bruck (Antimicrob Agents Chemother, 2017)
Changes in the pharmacokinetics of piperacillin in febrile neutropenic patients have been reported to result in suboptimal exposures. This study aimed to develop a population pharmacokinetic model for piperacillin and perform dosing simulation to describe optimal dosing regimens for hematological malignancy patients with febrile neutropenia. Concentration-time data were obtained from previous prospective observational pharmacokinetic and interventional therapeutic drug monitoring studies. Nonparametric population pharmacokinetic analysis and Monte Carlo dosing simulations were performed with the Pmetrics package for R. A two-compartment model, with between-subject variability for clearance (CL), adequately described the data from 37 patients (21 males, age of 59 ± 12 years [means ± standard deviations] and weight of 77 ± 16 kg). Parameter estimates were CL of 18.0 ± 4.8 liters/h, volume of distribution of the central compartment of 14.3 ± 7.3 liters, rate constant for piperacillin distribution from the central to peripheral compartment of 1.40 ± 1.35 h(−1), and rate constant for piperacillin distribution from the peripheral to central compartment of 4.99 ± 7.81 h(−1). High creatinine clearance (CL(CR)) was associated with reduced probability of target attainment (PTA). Extended and continuous infusion regimens achieved a high PTA of >90% for an unbound concentration of piperacillin remaining above the MIC (fT(>MIC)) of 50%. Only continuous regimens achieved >90% PTA for 100% fT(>MIC) when CL(CR) was high. The cumulative fraction of response (FTA, for fractional target attainment) was suboptimal (<85%) for conventional regimens for both empirical and directed therapy considering 50% and 100% fT(>MIC). FTA was maximized with prolonged infusions. Overall, changes in piperacillin pharmacokinetics and the consequences on therapeutic dosing requirements appear similar to those observed in intensive care patients. Guidelines should address the altered dosing needs of febrile neutropenic patients exhibiting high CL(CR) or with known/presumed infections from high-MIC bacteria.